Dating New Zealand Business Cycles - Kim, Kunhong; Buckle, R.A; Hall, V.B (School of Management Working Papers, 1994)
Dating the turning points and durations of business cycles has long been associated with NBER type reference cycle indexes. More recently, such work has become additionally important for evaluating modern theoretical business cycle models and for analysing the time varying characteristics of cycles. This paper applies the relatively simple and transparent Bry and Boschan business cycle dating procedure to four New Zealand real gdp series; compares the resulting turning points with those previously identified using NBER type cycle identification techniques, and with those obtained from three relatively mechanistic "deviations from trend" methods; provides some empirical benchmark turning point and cycle duration characteristics; and as a prelude to further theoretical and empirical work, compares these with results obtained from a number of potentially relevant AR and 1(1) statistical processes.